2010
DOI: 10.5194/acp-10-5979-2010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UV irradiances from Aura/Ozone Monitoring Instrument (OMI) with Brewer measurements at El Arenosillo (Spain) – Part 1: Analysis of parameter influence

Abstract: Abstract. The main objective of this study is to compare the erythemal UV irradiance (UVER) and spectral UV irradiances (at 305, 310 and 324 nm) from the Ozone Monitoring Instrument (OMI) onboard NASA EOS/Aura polar sun-synchronous satellite (launched in July 2004, local equator crossing time 01:45 p.m.) with ground-based measurements from the Brewer spectrophotometer #150 located at El Arenosillo (South of Spain). The analyzed period comprises more than four years, from October 2004 to December 2008. The effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
5
31
0
15
Order By: Relevance
“…This is consistent with the results obtained by Antón et al (2009Antón et al ( , 2010a in their study conducted for the Iberian Peninsula. This reduction, along with the reduced standard deviation, indicates that the spread between the datasets decreased due to launching more modern satellite instruments and the repair of the algorithms of the satellite instruments, performed over time (Bhartia and Wellemeyer, 2002), in addition to the substitutions of the ground equipment that occurred during these periods.…”
Section: Daily and Monthly Analysis/comparisonssupporting
confidence: 83%
See 2 more Smart Citations
“…This is consistent with the results obtained by Antón et al (2009Antón et al ( , 2010a in their study conducted for the Iberian Peninsula. This reduction, along with the reduced standard deviation, indicates that the spread between the datasets decreased due to launching more modern satellite instruments and the repair of the algorithms of the satellite instruments, performed over time (Bhartia and Wellemeyer, 2002), in addition to the substitutions of the ground equipment that occurred during these periods.…”
Section: Daily and Monthly Analysis/comparisonssupporting
confidence: 83%
“…Figure 2 shows the scatterplot plotted for Brewer spectrophotometer data and satellite data. (Viatte et al, 2011;Antón et al, 2009Antón et al, , 2010a; Rome, Italy (Ialongo et al, 2008); and at other monitoring stations around the planet (Hendrick et al, 2011;Keckhut et al, 2010).…”
Section: Daily and Monthly Analysis/comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a companion paper (Antón et al, 2010) the effect of several factors as clouds, aerosols, ozone and the solar elevation on OMI-Brewer UV bias were analysed and compared with previous TOMS-Brewer results (Antón et al, 2007). In the previous works, as in Antón et al (2010), the aerosol effect was studied in terms of aerosol extinction optical depth (AOD) measured at visible 440 nm wavelength. The comparison results showed that under moderate-high aerosol load (AOD(440 nm) > 0.25) the OMI bias is about 19-15% for UVER and spectral UV irradiances.…”
Section: Introductionmentioning
confidence: 99%
“…Most of this positive bias is attributed to boundary layer aerosol absorption that is not accounted for in the TOMS/OMI operational UV algorithm. Therefore, the main objective of this study is to analyse the aerosol effect on the bias between OMI erythemal UV irradiance (UVER) and spectral UV (305 nm, 310 nm and 324 nm) surface irradiances and ground-based The effects of other factors as clouds, ozone and the solar elevation over this intercomparison were analysed in detail in a companion paper (Antón et al, 2010). In that paper the aerosol effects were studied making only a rough evaluation based on aerosol optical depth (AOD) information at 440 nm wavelength (visible range) without applying any correction.…”
mentioning
confidence: 99%